PROGRAM APPLICATION DATA VALUE PHYSYCAL EDUCATION MADRASAH IBTIDAIYAH TARBIYAH ISLAMIYAH PONDOK AREN MICROSOFT VISUAL BASIC USING 6.0 - Muhammad Badruzaman; Ire Puspa Wardhani, S.Kom.,MMSI (Jurnal Sistem Informasi, 2004)
School is a place to seek knowledge, of which has not been understood to understand.School MI Islamiyah tarbiyah first school was built at this school Pondok Arenrequire computer equipment and programs, to access the data value of studentsperbidang study, so teachers do not need to record the value of students bookedbecause of where the book value recorded data like missing. So with that we are theauthors provide students the value of the data program using Visual Basic 6.0application program which the program is not too difficult to handle in a recordwhere the value of direct student unprocessed.Visual Basic program was helpful in dealing with everything that is in good schoolsfor the Guardian class that handles about rapot students and data for the Tata businessthat handles financial management.